An Efficient and Convenient Method for Desilylation-Acetylation of Trimethylsiyl Ethers Catalyzed by Silica Sulfuric Acid - Jin, Tong-Shou; Lin, Rui-Nian; Li, Yan-Wei; Li, Meng; Li, Tong-Shuang (Asian Journal of Chemistry, 2010)
An efficient and convenient method for desilylation-acetylation of trimethylsiyl ethers with acetic anhydride using silica sulfuric acid as catalyst under mild conditions is described.